Quality analysis of Areca catechu L varieties from Mekong delta, in VietNam - Thi, Lang Nguyen; Chi, Hieu Bui; Le, Khang Minh; Nguyen, Phuoc Trong (International Journal of Environment, Agriculture and Biotechnology, 2023)
The areca nut palm (Areca catechu L., Arecaceae family) is an economically important palm species in the World providing livelihood options to millions of farmers. The objectives of this study were to extract from areca nut to determine the The phenolic content (TPC) , The flavonoid content (TFC) and Anthocyanin content (TAC) content of 8 samples areca nut in the Mekong Delta .TPC of different sample differed significantly (p < 0.05). The TPC measured in areca nut was significantly higher ( 135.78-162.27 mg). There were significant differences in the flavonoid content in areca nut (p < 0.05). The Anthocyanin contents in areca nut were in the range of ( 23.55-35.55mg). The contents of TFC of different arecanut palm sites were significantly different (p < 0.05) The TFC measured was significantly higher (365.71–495.12mg) . The trend of flavonoid content of different sites was similar to that of total phenolic content .Alkaloid levels in 8 Areca Nut at difference sites analysis .The content associated Alkaloid in eight varieties with different genotypes such as Guvacine ,arecoline , Arecaidine and arecoline in hoblies in different districts of Mekong were compared. The DPPH radical-scavenging rate significantly varied in different sites (34.6 to 66.9% p < 0.05). According to the differences of functional substances among varieties, it can provide guidance for consumers and theoretical basis for the production of healthy food.